2021
DOI: 10.3389/fpsyt.2021.736094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Frequency rTMS on Negative Symptoms and Cognitive Function in Hospitalized Patients With Chronic Schizophrenia: A Double-Blind, Sham-Controlled Pilot Trial

Abstract: This study aimed to evaluate the efficacy of high-frequency repetitive transcranial magnetic stimulation (rTMS) over left dorsolateral pre-frontal cortex (DLPFC) in ameliorating negative symptoms and cognitive impairments in patients with chronic schizophrenia. Fifty-two patients with chronic schizophrenia were randomly assigned to two groups: active rTMS group and sham rTMS group, with existing antipsychotic drugs combined 20 sessions of 10 Hz active/sham rTMS over DLPFC (20 min/session, 5 times/week). The PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…A recent 10-year follow-up study reported that schizophrenia patients with sustained negative symptoms could have a poorer cognitive function and a lower level of global functioning compared to patients with an early illness course characterized by the absence of negative symptoms ( 33 ). In addition, transcranial direct current stimulation (tDCS) or repetitive transcranial magnetic stimulation (rTMS) can ameliorate the negative symptoms and further improve cognitive function in schizophrenia patients ( 34 , 35 ). The greater extent of cognitive deficits among DS patients than among NDS patients found in our present study further supports the above causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…A recent 10-year follow-up study reported that schizophrenia patients with sustained negative symptoms could have a poorer cognitive function and a lower level of global functioning compared to patients with an early illness course characterized by the absence of negative symptoms ( 33 ). In addition, transcranial direct current stimulation (tDCS) or repetitive transcranial magnetic stimulation (rTMS) can ameliorate the negative symptoms and further improve cognitive function in schizophrenia patients ( 34 , 35 ). The greater extent of cognitive deficits among DS patients than among NDS patients found in our present study further supports the above causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…B. Although with very high uncertainty, this safety analysis found no effect on positive symptoms (mean [SD] duration, 3.9 [2.0] weeks; 14 studies 53,59,71,[95][96][97][98]105,115,117,119,120,122,123 ; 909 participants; Ο‡ 2 = 0.05; df = 2; P = .98; I 2 = 75%). C. Although with very high uncertainty for high dose, a bell-shape curve was obtained (mean [SD] duration, of 1.7 [0.5] weeks; 5 studies 24,34,53,91,122 ; 159 participants; Ο‡ 2 = 36.52 df = 2; P < .001; I 2 = 95%).…”
Section: Current Depressive Episodementioning
confidence: 75%
“…We included 110 studies, encompassing a total of 4820 participants . The majority of participants were male (2959 [61.4%] compared with 1861 females [38.6%]), and the mean (SD) age was 43 (8.8) years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies had reported similar benefits of high-frequency rTMS on negative symptoms in patients with schizophrenia. A double-blind, sham-controlled, high-frequency rTMS study demonstrated that the rTMS group showed effective amelioration of negative symptoms, indicating that rTMS may have potential benefits in improving clinical symptoms and cognitive functions in patients with chronic schizophrenia ( Wen et al, 2021 ). Moreover, a high-frequency (20 Hz) unilateral rTMS over the left DLPFC suggested that rTMS may lead to an improvement in the negative symptoms of schizophrenia ( Kumar et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%